Analisis Pengelolaan Keuangan dan Pengeluaran Daerah Terhadap Pendapatan Masyarakat di Kabupaten Simalungun - Wico Jontarudi Tarigan; Djuli Sjafei Purba; Mahaitin H Sinaga (Universitas Negeri Padang, 2023)
In order to create public welfare and be able to enhance community welfare, the government must be able to manage the available resources. This study was conducted to determine the impact of government spending and budget management on the income of residents in Simalungun Regency. Data were gathered for this study using the purposive sampling technique to obtain secondary data for each variable. Multiple linear regression is the data analysis method employed, and the F test and t test are used to examine the significance of the effect jointly. The partial regression coefficients are tested using the t test. The heteroscedasticity test, multicollinearity test, and autocorrelation test were all performed as part of the standard assumption test. The results of this study demonstrate that budget management and government expenditure have a positive and significant impact on people's incomes concurrently and in part. In this study, these two variables correctly predicted the income of Simalungun Regency residents 96% of the time, with the remaining 4% being influenced by additional variables not included in the research model.